2022
DOI: 10.3390/nu14020372
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nutritional Strategies on Improving the Quality of Diet of Children from 6 to 12 Years Old: A Systematic Review

Abstract: Dietary habits, that are formed during childhood and consolidated in adulthood, are known to influence the development of future chronic diseases such as metabolic syndrome or type 2 diabetes. The aim of this review was to evaluate the effectiveness of nutritional interventions carried out in recent years focused on improving the quality of the diet of the child population. A systematic search of the PubMed and Scopus databases was performed from January 2011 until September 2021. A total of 910 articles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Overall diet quality is not often assessed in family web-based interventions [10] which makes it difficult to compare these results with other studies. A recent review focussing on effectiveness of nutritional strategies on improving diet quality in children (which only include three studies with parents out of twelve), found that most studies assessed diet quality or dietary patterns mainly by focussing on an increase consumption of foods considered as healthy (fruits and vegetables) and a decrease in those less healthy (sugary drinks, less healthy snacks) [43]. In our study, overall diet quality was assessed using the NRF9.3, which has been validated with the Healthy Eating Index [32,33].…”
Section: Table 2 Daily Vegetables and Fruit Mean Intakes Nutrient Int...mentioning
confidence: 99%
“…Overall diet quality is not often assessed in family web-based interventions [10] which makes it difficult to compare these results with other studies. A recent review focussing on effectiveness of nutritional strategies on improving diet quality in children (which only include three studies with parents out of twelve), found that most studies assessed diet quality or dietary patterns mainly by focussing on an increase consumption of foods considered as healthy (fruits and vegetables) and a decrease in those less healthy (sugary drinks, less healthy snacks) [43]. In our study, overall diet quality was assessed using the NRF9.3, which has been validated with the Healthy Eating Index [32,33].…”
Section: Table 2 Daily Vegetables and Fruit Mean Intakes Nutrient Int...mentioning
confidence: 99%
“…Given the changes in food consumption, the improvement in dietary pro le is not surprising [40][41][42], however, it is not very often reported. A recently published review showed that only a 33% of the interventional studies focused on improving children's diet quality reported the nutrient distribution of participant's diet [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be noted that when programs not only focus on improving a specific healthy habit, but rather on the development of nutritional strategies focused on the acquisition of a healthy lifestyle as a whole, which includes physical activity, they are more effective; both China and the Netherlands were able to carry out this type of program [ 223 , 224 ]. The duration of the intervention period varied depending on the study; however, the most successful programs had a duration equal to or greater than one academic year [ 225 ].…”
Section: Specific Policies To Promote Healthy Dietary Patterns From I...mentioning
confidence: 99%